Global successful experiences of the health tourism brand and presentation of a native model - Afsharifar, Amin (Revista de la Universidad del Zulia, 2020)
The current study aims to benchmark the global successful experiences of health tourism branding and presenting its native pattern. This study is analytical-descriptive in nature and practical approach in terms of the target sought. The questionnaire was designed to measure the effective variables on health tourism branding. A researcher-made questionnaire, whose dimensions and indicators were based on the literature and research background, was used to measure the dependent variable of the research. Acer brand value questionnaire was used for assessing the dependent variable of the research. The statistical population of this research is the professors of the medical sciences universities and tourism and marketing management group and the directors and assistants of the Cultural Heritage, Handicrafts and Tourism Organization of Fars and Bushehr provinces that regarding the lack of access to all members of the research community, sampling was done by available sampling. Finally, 87 valid questionnaires were obtained. After examining the research model using the path analysis method, the findings showed that all paths between the research variables were confirmed at 95% confidence level and were significant. This means that policy making, infrastructure, marketing, communication and information, medicine and health have a positive and significant impact on health tourism branding. However, the findings indicated that the highest path coefficient for the relationship between the infrastructure and branding of health tourism is 0.365.